Respuesta :

Answer:

(x - 3)²/3² - (y + 4)²/2² = 1 ⇒ (0 , -4) , (6 , -4)

(x - 4)²/7² - (y + 6)²/5² = 1 ⇒ (-3 , -6) , (11 , -6)

(y + 5)²/5² - (x - 4)²/8² = 1 ⇒ (4 , 0) , (4 , -10)

(y + 7)²/7² - (x + 2)²/4² = 1 ⇒ (-2 , 0) , (-2 , -14)

(x + 1)²/9² - (y - 1)²/11² = 1 ⇒ (8 , 1) , (-10 , 1)

Step-by-step explanation:

* Lets revise the standard form of the equations of the hyperbola

- The standard form of the equation of a hyperbola with  center (h , k)

 and transverse axis parallel to the x-axis is  (x - h)²/a² - (y - k)²/b² = 1

- The coordinates of the vertices are (h ± a , k)

- The standard form of the equation of a hyperbola with center (h , k)

 and transverse axis parallel to the y-axis is  (y - k)²/a² - (x - h)²/b² = 1

- The coordinates of the vertices are (h , k ± a)

* Lets solve the problem

# (x - 3)²/3² - (y + 4)²/2² = 1

∵ (x - h)²/a² - (y - k)²/b² = 1

∴ a = 3 , b = 2 , h = 3 , k = -4

∵ The coordinates of the vertices are (h ± a , k)

∴ The coordinates of the vertices are (3 - 3 , -4) , (3 + 3 , -4)

∴ The coordinates of the vertices are (0 , -4) , (6 , -4)

* (x - 3)²/3² - (y + 4)²/2² = 1 ⇒ (0 , -4) , (6 , -4)

# (y - 1)²/2² - (x - 7)²/6² = 1

∵ (y - k)²/a² - (x - h)²/b² = 1

∴ a = 2 , b = 6 , h = 7 , k = 1

∵ The coordinates of the vertices are (h , k ± a)

∴ The coordinates of the vertices are (7 , 1 - 2) , (7 , 1 + 2)

∴ The coordinates of the vertices are (7 , -1) , (7 , 3)

* No answer for this equation

# (x - 4)²/7² - (y + 6)²/5² = 1

∵ (x - h)²/a² - (y - k)²/b² = 1

∴ a = 7 , b = 5 , h = 4 , k = -6

∵ The coordinates of the vertices are (h ± a , k)

∴ The coordinates of the vertices are (4 - 7 , -6) , (4 + 7 , -6)

∴ The coordinates of the vertices are (-3 , -6) , (11 , -6)

* (x - 4)²/7² - (y + 6)²/5² = 1 ⇒ (-3 , -6) , (11 , -6)

# (y + 5)²/5² - (x - 4)²/8² = 1

∵ (y - k)²/a² - (x - h)²/b² = 1

∴ a = 5 , b = 8 , h = 4 , k = -5

∵ The coordinates of the vertices are (h , k ± a)

∴ The coordinates of the vertices are (4 , -5 + 5) , (4 , -5 - 5)

∴ The coordinates of the vertices are (4 , 0) , (4 , -10)

* (y + 5)²/5² - (x - 4)²/8² = 1 ⇒ (4 , 0) , (4 , -10)

# (y + 7)²/7² - (x + 2)²/4² = 1

∵ (y - k)²/a² - (x - h)²/b² = 1

∴ a = 7 , b = 4 , h = -2 , k = -7

∵ The coordinates of the vertices are (h , k ± a)

∴ The coordinates of the vertices are (-2 , -7 + 7) , (-2 , -7 - 7)

∴ The coordinates of the vertices are (-2 , 0) , (-2 , -14)

* (y + 7)²/7² - (x + 2)²/4² = 1 ⇒ (-2 , 0) , (-2 , -14)

# (x + 1)²/9² - (y - 1)²/11² = 1

∵ (x - h)²/a² - (y - k)²/b² = 1

∴ a = 9 , b = 11 , h = -1 , k = 1

∵ The coordinates of the vertices are (h ± a , k)

∴ The coordinates of the vertices are (-1 + 9 , 1) , (-1 - 9 , 1)

∴ The coordinates of the vertices are (8 , 1) , (-10 , 1)

* (x + 1)²/9² - (y - 1)²/11² = 1 ⇒ (8 , 1) , (-10 , 1)

Answer:

(x - 3)²/3² - (y + 4)²/2² = 1 ⇒ (0 , -4) , (6 , -4)

(x - 4)²/7² - (y + 6)²/5² = 1 ⇒ (-3 , -6) , (11 , -6)

(y + 5)²/5² - (x - 4)²/8² = 1 ⇒ (4 , 0) , (4 , -10)

(y + 7)²/7² - (x + 2)²/4² = 1 ⇒ (-2 , 0) , (-2 , -14)

(x + 1)²/9² - (y - 1)²/11² = 1 ⇒ (8 , 1) , (-10 , 1)